Treatment of COPD groups GOLD A and B with inhaled corticosteroids in the COSYCONET cohort: determinants and consequences - Lutter, Johanna I.; Jörres, Rudolf A.; Trudzinski, Franziska; Alter, Peter; Kellerer, Christina; Watz, Henrik; Welte, Tobias; Bals, Robert; Kauffmann-Guerrero, Diego; Behr, Jürgen; Holle, Rolf; Vogelmeier, Claus F.; et al. (The International journal of chronic obstructive pulmonary disease, 2021)
GOLD A and B COPD patients are often treated with inhaled corticosteroids (ICS), which may benefit only a subgroup of these patients. Click to read more.
Gesehen am 18.05.2021